Optimized surgical treatment and study management for oncology patients in East Saxony (MISSION4Sax): study protocol of a multicentre pilot study - Christin Richter; Anne Döring; Floris Berg; Michelle Roost; Andreas Hasselberg; Carola Martin; Hannes Schlieter; Daniela Piontek; Olaf Schoffer; Jochen Schmitt; Jürgen Weitz; Grit Krause-Jüttler; et al. (Journal of Cancer Research and Clinical Oncology, 2026)
Abstract Purpose MISSION4Sax aims to develop and pilot new concepts for cross-sectoral oncological care, data integration and networking between maximum care centres and rural practitioners in medical underserved, enabling access to guideline-based therapy, innovative surgery, and clinical trials. Methods This pilot project is an exploratory multicentre, prospective longitudinal study. It assesses the feasibility, acceptability, implementation and data-quality aspects of the proposed care model and study infrastructure, rather than to determine the effectiveness or causal impact of the interventions. It implements an interdisciplinary, cross-sectoral care model centred on a regional surgical indication tumour board at the National Center for Tumor Diseases (NCT) Dresden. Evidence-based, standardised patient care pathways are developed and piloted across three regional hospitals and two oncology practices. A database using the infrastructure of the NCT Core Unit “Registry Trial Platform”, targeted training programmes and “Flying Data Nurses” support coordination, data flow and communication. Patient-reported outcomes complement the clinical data. Routinely collected health insurance data will be used exclusively as external reference data for a descriptive comparison with the MISSION4Sax cohort; no individual-level data linkage will be performed. A mixed-methods process evaluation will be performed alongside the project. Expected outcomes The study will assess feasibility in routine care and explore access to specialised care, waiting times, coordination, pathway adherence, and clinical and patient-reported outcomes. Conclusion Strengthening cancer care infrastructure, interdisciplinary cooperation, and digital systems may support equitable access to high-value care in rural regions. The proposed tumour board, patient pathways, and trained staff may improve care quality and collaboration across sectors. Trial registration DRKS00036134 (registration date: 30 June 2025)